Infant wellbeing and monitoring: An observation of the Road to Health Booklet in Masiphumelele - Ngcowa, Sonwabiso (School of African and GenderStuds, Anth and Ling, 2020)
The South African government monitors and tracks the health of newborns and the growth of children. The Department of Health (DoH) does this monitoring using the Road to Health Booklet (RtHB). In this dissertation I analyse the use of the booklet in the township of Masiphumelele in Cape Town. The state produced booklet is intended for the child and mother as a patient-held medical health record. Liaw (1993) defines a patient-held record as notes or space provided on a document for the recording of follow up appointments for further investigation by medical doctors. The RtHB is used to record the child’s development, immunisations and HIV related information from birth to the age of twelve years. The dissertation results from ethnographic research with eight black Xhosa1 mothers and caregivers with children under the age of five years old. Mosley, and Chen, (1984), argue that in developing countries where standard child healthcare has been made available, children should survive the first five years of life. In my research, during the period of six weeks between July, August and September 2017, I followed the booklet in to Masiphumelele. From my observation and semi-structured interviews, looking at the state’s role of ‘pastoral’ care, child wellbeing and living in a township, and recording, under the theme of child wellbeing, certain concepts emerged. These concepts were state power, mothering, caring for children, responsibilisation, gender, kinship, fatherhood, child wellbeing knowledge production, social networking. In this dissertation I use ethnographic findings, accompanied by my own personal narratives. I argue that tracking child wellbeing through this booklet, the state exercises what Foucault (1982) referred to as ‘pastoral power’ in ensuring the wellbeing of the populations.